√3x2 + 4x + √3
⟹ √3x2 + 3x + x + √3
⟹ √3x (x + √3) + 1 (x + √3)
⟹ (x + √3) (√3x + 1)
Therefore, the factors of the given polynomial = (x + √3) (√3x + 1)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :